Chronic Hepatitis B In Elite Athletes - T. H. Nguyen; L. Yu. Ilchenko; K. K. Kyuregyan; L. I. Melnikova; C. C. Nguyen (Архивъ внутренней медицины, 2025)
Athletes, as well as other general population groups, are at risk of infection with hepatitis viruses.The aim of the study was to characterise the clinical and virological picture of chronic hepatitis B (CHB) in athletes and to evaluate the efficacy of antiviral therapy.Materials and Methods. Forty-two elite athletes with CHB were included in the study. The results of clinical and laboratory (including virological) parameters and data of instrumental methods of examination were analysed. The efficacy of antiviral therapy was evaluated by virological, serological, biochemical responses and reduction of liver fibrosis severity.Results. 35.7 % of athletes periodically reported heaviness in the right hypochondrium, and 19 % experienced mild weakness. Diffuse changes in the liver were detected in two-thirds (66.7 %) of the athletes. Additionally, 19.4 % exhibited liver enlargement and/or splenomegaly, while 29.0 % showed moderate or signiﬁcant liver ﬁbrosis. Elevated ALT activity was observed in 31.0 % of the athletes. Hepatitis B virus DNA was found in the blood serum of all athletes, with 73.8 % of cases showing a viral load of ≥200 IU/mL. During treatment with nucleos(t) ide analogs, aviremia and normalization of aminotransferase activity were achieved in all cases within 3.0 and 4.5 months, respectively. Stabilization or reduction in the severity of liver ﬁbrosis was observed in 90.9 % of athletes after 24.0 months. Viremia recurrence was noted in 7 out of 17 cases due to drug discontinuation.Conclusion. The clinical presentation of CHB in athletes is characterized by minimal symptoms. After a relatively short period, antiviral therapy with nucleos(t)ide analogs demonstrated high efﬁcacy in achieving virological and biochemical responses, as well as in reducing the severity of liver ﬁbrosis. Cases of viremia recurrence were associated with discontinuation of the medications.